Theoretical and experimental analysis of compressive residual stress field on 6061 aluminum alloy after ultrasonic surface rolling process. (August 2019) - Meng, Zhang; Yuanxi, Zhang; Yang, Zhou
Ultrasonic surface rolling process is a mechanical surface treatment used for improving fatigue life by introducing a compressive residual stress field into the surface of metallic components. This paper develops a simplified theoretical analysis model of compressive residual stress field induced by ultrasonic surface rolling process. Explicit dynamic solution in ABAQUS is used for calculating the plastic contact radius ap and velocity V 0 of the tool tip. Afterward, compressive residual stress field is predicted by using MATLAB on the basis of this theoretical model. Additionally, ultrasonic surface rolling process experiments are conducted to verify the calculated results of compressive residual stress field. The influence of ultrasonic surface rolling process parameters on compressive residual stress field, such as static force F 0, spindle speed n, vibration amplitude B, and ultrasonic frequency f, are examined by using theoretical analysis and experiments. The calculated results of compressive residual stress field are in relatively good agreement with the experimental results. Furthermore, ap essentially determines the distribution of compressive residual stress field. Other parameters indirectly affect the distribution of compressive residual stress field through changing ap . Finally, static force and vibration energy simultaneously applied to the tool tip can significantly affect the distribution of compressive residual stress field compared with only static force.